Survival strategies of internal security in Nigeria: the amotekun option / Oikhala Gabriel Izokpu - Izokpu, Oikhala Gabriel (Universiti Teknologi MARA, 2022)
Across the world, governments guarantee security of citizens and provide enabling environment for people to go about their lawful business. In Nigeria, incessant kidnappings, attacks on farmers by herdsmen, ritual killings, and bombings by Boko Haram among others are forcing people to live in fear and can no longer go about their legitimate business. The level of insecurity at present has degenerated to where efforts of the Nigeria police appeared not helpful. With this development, the South-West Governors organised Security Summit and established a regional security labelled “Amotekun” to rid the region of criminal elements. This paper examined the legality of Amotekun security outfit and causes of security breakdown in Nigeria. Relevant data were obtained from textbooks, journals, and newspapers among others. Data collected were analysed through descriptive method. Using the Grand Strategy for Internal Security Narrative as a framework, Amotekun was established to fight crimes and stop herdsmen and Boko Haram terrorist activities in South West. The paper found Amotekun as inconsistent with the Constitution. It found bad governance, poor leadership, injustice, weak law enforcement, and unemployment as some causes of security breakdown in Nigeria. It concluded that the establishment of Amotekun as a regional security is illegal and hence, it cannot improve the security breakdown in Nigeria. The paper recommended that the police should adopt comprehensive policing; the federal government should maintain efficient police and stop intermingling security issues with politics; and the South-West governments should push for constitutional review to recognise regional police in Nigeria.